2019
DOI: 10.3389/fncom.2019.00015
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram-Based Single-Trial Detection of Language Expectation Violations in Listening to Speech

Abstract: We propose an approach for the detection of language expectation violations that occur in communication. We examined semantic and syntactic violations from electroencephalogram (EEG) when participants listened to spoken sentences. Previous studies have shown that such event-related potential (ERP) components as N400 and the late positivity (P600) are evoked in the auditory where semantic and syntactic anomalies occur. We used this knowledge to detect language expectation violation from single-trial EEGs by mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…It is likely that their higher accuracy reflects the better data quality recorded in adults, who are better able to sit still and engage with the task. More recently, Tanaka et al reported significant decoding of single-trial semantic anomalies, with an overall accuracy of 59.5% 53 . They, however, did not report individualparticipant accuracies, making it hard to compare their results to the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that their higher accuracy reflects the better data quality recorded in adults, who are better able to sit still and engage with the task. More recently, Tanaka et al reported significant decoding of single-trial semantic anomalies, with an overall accuracy of 59.5% 53 . They, however, did not report individualparticipant accuracies, making it hard to compare their results to the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have reported single-trial classification rates in the order of 0.8 (see Reference [ 58 , 59 , 65 ]). The classification rates reported are similar to those achieved in this work.…”
Section: Discussionmentioning
confidence: 99%
“…First, the effect of stimulation condition and of the number of symbols on the single-trial classification between target and non-target responses was assessed through a five-fold cross-validation process. Although there exist a sample overlapping, this performance evaluation approach is quite acceptable to estimate the online performance of the BCI [ 58 , 59 ]. Here, all the epochs in a given dataset were randomly allocated into five sets.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that their higher accuracy reflects the better data quality recorded in adults, who are better able to sit still and engage with the task. More recently, Tanaka et al (2019) reported significant decoding of single-trial semantic anomalies, with an overall accuracy of 59.5%.…”
Section: Discussionmentioning
confidence: 99%